Nota krytyczna o książce Sanctuary for All Life: The Cowbala of Jim Corbett - Poks, Małgorzata (Er(r)go. Teoria - Literatura - Kultura, 2017)
A critical note on the book: Jim Corbett, Sanctuary for All Life: The Cowbala of Jim Corbett (Berthoud, Co: Howling Dog Press, 2005), pp. 328.